Social Stability Related to Sex Group Composition in the Cichlid Nile Tilapia - Carvalho, Thaís Billaba; Freitas, Eliane Gonçalves de [UNESP] (My University, 2011)
Aquaculture practices usually put the Nile tilapia in an artificial social environment, which males predominate due to their faster growth desirable for aquaculture purposes. Such a situation can increase male-male fighting because males are generally more aggressive than females, and also because fighting ability is similar within the same sex, leading to longer contests. As behavior has been used to infer welfare in several fish species, the aim of this study was to investigate whether sex composition affects agonistic interactions, social hierarchy and energetic demand in groups of Nile tilapia (Oreochromis niloticus; L.). Size-matched adult fish were divided in two treatments: MM = four males and MF = two males and two females (10 repetitions for each treatment). The experiment lasted for 11 days and social interactions (aggressiveness and rank order) were recorded at the 2nd, 6th and 10th days (15 min per day). Fish were food deprived and body weight loss was used to infer energetic cost. A higher frequency of lateral threat (Student’s t independent test; t = 2.55; p = 0.02) and total interactions (Student’s t independent test; t = -2.81; p = 0.01) was observed in the MF treatment. MM group showed unstable hierarchy (Binomial test, p = 0.04), which is considered a social stressor. However, mean weight loss was not affected by treatments (Student’s t independent test; t = -0.74; p = 0.47). These results support the idea that sexual composition affects aggressive interactions and destabilizes social hierarchy, but not energy cost
Keywords: aggresiveness; social rank; Cichlid fish